Altered Intrinsic Regional Spontaneous Brain Activity in Patients With Severe Obesity and Meibomian Gland Dysfunction: A Resting-State Functional Magnetic Resonance Imaging Study - Liu, Yi; Tan, Sheng-Xing; Wu, Yu-Kang; Shen, Yan-Kun; Zhang, Li-Juan; Kang, Min; Ying, Ping; Pan, Yi-Cong; Shu, Hui-Ye; Shao, Yi (Frontiers in Human Neuroscience, 2022)
Purpose: To evaluate potential regional homogeneity (ReHo) cerebrum function lesions in people with severe obesity and meibomian gland dysfunction (SM) and probe the connection between aberrant cerebrum activity and clinical manifestations. Patients and methods: An aggregation of 12 patients with SM, and 12 healthy controls (HCs) closely matched in age and gender were enrolled. We applied corneal confocal microscopy and fundus angiography to compare imaging distinctions between the two groups. ReHo was also utilized to appraise partial differences in spontaneous cerebrum function. Results: ReHo values for the left cerebellum (LC), right fusiform gyrus (RFG), left inferior temporal gyrus (LITG), left rectus gyrus (LRG), right thalamus (RT), right caudate (RC), left insula (LI), and left thalamus (LT) of subjects with SM were notably higher than those of the HCs (P < 0.05). ReHo values of the right middle frontal gyrus (RMFG) in subjects with SM were decreased notably compared to the HCs (P < 0.05). Conclusion: Our research emphasized that patients with SM had lesions in synchronized neural activity in many encephalic areas. Our discoveries may provide beneficial information for exploring the neuromechanics of SM.